Characterization and population diversity of Erwinia amylovora strains originating from pome fruits in Serbia - Krivokapić, Marija; Gavrilović, Veljko; Ivanović, Milan; Kuzmanović, Nemanja; Fira, Đorđe; Obradović, Aleksa; Gašić, Katarina (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2018)
The diversity of 30 Erwinia amylovora strains, isolated from quince, pear and apple trees on 14 localities in Serbia, was studied using bacteriological and molecular methods. In pathogenicity tests, all strains caused necrosis and oozing of bacterial exudate on inoculated immature pear, cherry and plum fruits, and induced hypersensitive reaction in tobacco leaves. The studied strains were Gram and oxidase negative, non-fluorescent, levan and catalase positive and facultatively anaerobic. The strains did not reduce nitrates, but utilized citrate and produced acid from sorbitol, hydrolyzed gelatine, produced reducing substances from sucrose and grew in the presence of 5% NaCl, but not at 36ºC. Identity of the strains was confirmed by conventional and nested PCR methods. Rep-PCR with REP, ERIC and BOX primers resulted in amplification of several DNA fragments respectively, but showed no variation within the strains. However, different genetic profiles were obtained with RAPD-PCR by using six primers which enabled differentiation of the strains into four groups. Genetic differences between the studied strains did not correlate with the host plants, geographical origin or year of isolation.